2020
DOI: 10.1097/tp.0000000000003446
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Glycogen Synthase Kinase 3β Alleviates Chronic Renal Allograft Dysfunction in Rats

Abstract: Background. Chronic renal allograft dysfunction (CRAD) is a major condition that impedes the long-term survival of renal allografts. However, the mechanism of CRAD is obscure, and the effective strategies for controlling the progression of CRAD are lacking. The present study used a CRAD rat model to assess the effect of glycogen synthase kinase 3β (GSK-3β) inhibition on the development of CRAD. Methods. A classical F334-to-LEW orthotopic renal transplantation was performed on the CRAD group. The treatment grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
1
1
0
Order By: Relevance
“…Assessment of oxidative stress markers and inflammatory cytokines revealed that the levels of proinflammatory cytokines, such as TNF- α , CD68, and IL-6, were higher, whereas those of GSH, SOD, and CAT were lower in transplant rats than in control groups. These results demonstrate that oxidative stress and inflammation are involved in the pathogenesis of chronic renal allograft dysfunction, which is consistent with the findings of previous studies [ 15 , 27 , 28 ]. Pharmacological intervention plays a significant role in IRI damage.…”
Section: Discussionsupporting
confidence: 93%
“…Assessment of oxidative stress markers and inflammatory cytokines revealed that the levels of proinflammatory cytokines, such as TNF- α , CD68, and IL-6, were higher, whereas those of GSH, SOD, and CAT were lower in transplant rats than in control groups. These results demonstrate that oxidative stress and inflammation are involved in the pathogenesis of chronic renal allograft dysfunction, which is consistent with the findings of previous studies [ 15 , 27 , 28 ]. Pharmacological intervention plays a significant role in IRI damage.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, pretreatment with Li significantly reduced proteinuria and improved glomerular function in a mouse model of doxorubicin-or lipopolysaccharide-induced podocyte injury in mice [141]. Consistent with these findings, selective pharmacological or genetic inhibition of GSK-3β was shown to improve renal function in various models of kidney disorders in animals [142][143][144]. Support for these experimental data comes from clinical evidence indicating that chronic Li treatment leads to a slight (if any) decrease in glomerular function and a negligible incidence of CKD that are of questionable clinical significance [30,31,41,42,145].…”
Section: Discussionmentioning
confidence: 55%